Misleading thyroid-stimulating hormone results due to immunoassay interference: A case report - Goh, Kian Guan; Zakaria, Miza Hiryanti; Shahar, Mohammad Arif; Omar, Ahmad Marzuki (2017)
Background: Thyroid hormone assay interference is often misdiagnosed. Is has deep impact onto patient’s care as wrong interpretation of the results leads to wrong intervention. This case is to highlight the importance of recognizing immunoassay interference for thyroid stimulating-hormone (TSH) congenital hypothyroidism. Case report: the patient is a 22-year-old university student with congenital hypothyroidism, diagnosed at age 10 due to poor growth velocity and constipation. Sha was put on L-thyroxine replacement since diagnosis. Despite small body habitus (weight 42 kg and height 153,5 cm) she was on 1125 mcg of L-thyroxine per week (3.83 mcg/kg/day) due to persistently high TSH (8.558 uIU/mL) despite normal free T4 (19.47 pmol/L) and clinically euthyroid. There were episodes of iatrogenic hyperthyroidism due to over-replacement of L-thyroxine (free T4 48.96 pmol/L) and patient became thyrotoxic clinically. There were wide fluctuations of TSH reading (1.086 – 99.076 uIU/mL) despite normal free T4 values (10.66 – 17.1 pmol/L) and normal free T3 (4.6 pmol/L). Her thyroid function was repeated in different labs and showed relatively normal thyroid function (free T4 15.7 pmol/L and TSH 0.76 uIU/mL). Discussion: Thyroid hormone assay interference is a recognized entity in clinical laboratory settings. Failure to acknowledge will lead to inappropriate treatment and harm to the patients. There were cases of unnecessary surgical procedures and chemotherapy instituted to patients due to assay interference by human chorionic gonadotropin assays. In this case, it has led to excessive replacement of thyroxine hormone inducing clinical thyrotoxicosis, which can lead to cardiac arrhythmia or accelerated osteoporosis. Heterophilic antibodies to mouse antibodies, rheumatoid factors, and drug are among the common causes of TSH assay interference. Conclusion: It is important for clinician to recognize assay interference as a cause of deranged lab results. Communication among physicians and clinical pathologist is important to minimize this error.